2021
DOI: 10.1002/cmdc.202100144
|View full text |Cite
|
Sign up to set email alerts
|

6‐Methyl‐7‐Aryl‐7‐Deazapurine Nucleosides as Anti‐Trypanosoma cruzi Agents: Structure‐Activity Relationship and in vivo Efficacy

Abstract: Chagas disease is a tropical infectious disease resulting in progressive organ-damage and currently lacks efficient treatment and vaccine options. The causative pathogen, Trypanosoma cruzi, requires uptake and processing of preformed purines from the host because it cannot synthesize these de novo, instigating the evaluation of modified purine nucleosides as potential trypanocides. By modifying the pyrimidine part of a previously identified 7-aryl-7-deazapurine nucleoside, we found that substitution of a 6-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It has also long been known that protozoan nucleoside transporters mediate the uptake of cytotoxic nucleoside analogues including formycin B and tubercidin used in this study but also, e.g., adenosine arabinoside in T. gondii [ 18 ] and cordycepin in T. brucei [ 10 , 56 ]. Very recently, a class of 7-substituted,7-deaza analogues of adenosine and inosine have shown great promise against multiple protozoan pathogens [ 9 , 12 , 13 , 14 , 57 , 58 ], which is clearly mediated by uptake through nucleoside transporters [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also long been known that protozoan nucleoside transporters mediate the uptake of cytotoxic nucleoside analogues including formycin B and tubercidin used in this study but also, e.g., adenosine arabinoside in T. gondii [ 18 ] and cordycepin in T. brucei [ 10 , 56 ]. Very recently, a class of 7-substituted,7-deaza analogues of adenosine and inosine have shown great promise against multiple protozoan pathogens [ 9 , 12 , 13 , 14 , 57 , 58 ], which is clearly mediated by uptake through nucleoside transporters [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A well-studied example is the role of the TbAT1/P2 aminopurine transporter of T. brucei in the uptake of melaminophenyl arsenicals and diamidines [ 5 , 6 , 7 ]. In recent years, purine antimetabolites have been shown to be among the most effective classes of antiprotozoal compounds, with promising activities against Trypanosoma brucei [ 8 , 9 , 10 , 11 ], T. congolense [ 12 ], T. cruzi [ 13 ], Trichomonas vaginalis [ 14 ], and Leishmania spp. [ 15 ], among others, placing further emphasis on the pharmacological importance of nucleoside carriers.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Unfortunately, no sterile cure could be achieved despite its high capacity to fully suppress parasitaemia and provide 100% survival in mouse models of T. cruzi infection. 23 As observed with other purine nucleoside analogues, 22 , 47 , 48 Cpd 1 was inactive against BT despite its outstanding intracellular activity in infected CC cultures (EC 50 = 0.029 ± 0.006 μM) and L929 cell lines (EC 50 = 0.25 ± 0.17 μM). 23 At that time, the lack of in vivo sterilization by Cpd 1 was attributed at least in part to its inefficacy towards BT and/or to the short treatment period (only 5 days) adopted in the initial in vivo study.…”
Section: Discussionmentioning
confidence: 60%
“…Building further on our recent findings that 6-methyl-7-deazapurine nucleoside analogues may display improved selectivity ( Lin et al, 2021 ), the present study focused on expanding the SAR of 6-methyl-7-deazapurine ribonucleosides with non-aromatic substituents. Variation of the substituents at position 7 of 7-deaza-6-methyl-9-β- d -ribofuranosylpurine revealed that chloro ( 7 ), methyl ( 9 ) and ethyl ( 13 ) groups afforded low micromolar activity against T. cruzi , L. infantum and T. brucei spp.…”
Section: Discussionmentioning
confidence: 99%
“…1 (b)). A recent screening of a panel of tubercidin analogues with a privileged 7-(4-chlorophenyl) substituent indicated that upon substitution of a 6-methyl for a 6-amino group the anti-T. cruzi activity was largely retained, while the selectivity (vs. MRC-5 fibroblasts) was improved ( Lin et al, 2021 ). To expand the SAR, the present study aimed to synthesize mostly novel 7-substituted 6-methyl-7-deazapurine ribonucleosides with emphasis on non-aromatic substituents and assess their activity against the stated protozoan parasites.…”
Section: Introductionmentioning
confidence: 99%